Comparison of conventional and Alltech beef PN finishing programs: performance and carcass characteristics - Phelps, Kelsey J.; Miller, K. A.; Van Bibber-Krueger, Cadra L.; Sexten, Andrea K.; Jennings, J.; Depenbusch, Brandon E.; Gonzalez, John M.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
The objective of this study was to compare the feedlot and carcass performance of the PN Beef Program in relation to a conventional feedlot diet when both diets are combined with or without exogenous growth promotants.
Keywords: Beef; Feed additives; Feedlot; Carcass traits; Alltech PN Beef Program